Increasing the PV Hosting Capacity in Unbalanced Three-Phase Distribution Networks Through Reconfiguration with Closed-Loop Operation - Macedo, Leonardo H. [UNESP]; Vargas, Renzo; Home-Ortiz, Juan M. [UNESP]; Mantovani, José R.S. [UNESP]; Romero, Rubén [UNESP]; Catalão, João P.S. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This article presents a novel mixed-integer nonlinear linear programming (MINLP) model to increase the photovoltaic (PV) hosting capacity in unbalanced three-phase electrical distribution systems. The problem considers the optimal operation of capacitor banks and network reconfiguration with radial and closed-loop operation. The objective function maximizes the PV hosting capacity of the system. A set of linearization strategies are employed to convert the presented MINLP model into a mixed-integer linear programming (MILP) problem. By considering the MILP formulation, optimality is guaranteed by using off-the-shelf optimization solvers. Several tests are carried out using a 25-node unbalanced three-phase distribution system. When examining network reconfiguration with radial and closed-loop operation, the results demonstrate that the proposed formulation is effective in increasing the penetration of PV sources.
Keywords: Closed-loop operation; hosting capacity; mixed-integer linear programming; network reconfiguration; unbalanced three-phase electrical distribution networks